The ability of selected European countries to face the impending economic crisis caused by COVID-19 in the context of the global economic crisis of 2008 - Róbert Oravský; Peter Tóth; Anna Bánociová (Journal of Risk and Financial Management, 2020)
This paper is devoted to the ability of selected European countries to face the potential economic crisis caused by COVID-19. Just as other pandemics in the past (e.g., SARS, Spanish influenza, etc.) have had negative economic effects on countries, the current COVID-19 pandemic is causing the beginning of another economic crisis where countries need to take measures to mitigate the economic effects. In our analysis, we focus on the impact of selected indicators on the GDP of European countries using a linear panel regression to identify significant indicators to set appropriate policies to eliminate potential negative consequences on economic growth due to the current recession. The European countries are divided into four groups according to the measures they took in the fiscal consolidation of the last economic crisis of 2008. In the analysis, we observed how the economic crisis influences GDP, country indebtedness, deficit, tax collection, interest rates, and the consumer confidence index. Our findings include that corporate income tax recorded the biggest decline among other tax collections. The interest rate grew in the group of countries most at risk from the economic crisis, while the interest rate fell in the group of countries that seemed to be safe for investors. The consumer confidence index can be considered interesting, as it fell sharply in the group of countries affected only minimally by the crisis (Switzerland, Finland).
Keywords: 330; COVID-19; economic crisis; fiscal consolidation; linear panel model